PERAN LINGKUNGAN KELUARGA DAN LINGKUNGAN SOSIAL DALAM MEMBENTUK MINAT MAHASISWA UNTUK WIRAUSAHA DI BIDANG UKGS - Rahayu, Angraeni Sri; Chaerudin, Denden Ridwan; Fatimah, Siti; Laela, Dewi Sodja (Jurnal Terapi Gigi dan Mulut, 2025)
Government efforts in establishing UKGS are still small, which is around 30% of the total schools in Indonesia. UKGS is an alternative to developing entrepreneurship in the field of dental health. Entrepreneurship education in the Department of Dental Health is provided with the aim that students have the ability to implement entrepreneurial principles. This study aims to determine the role of family environment, social environment and interest in entrepreneurship in shaping students' interest in entrepreneurship. This research is descriptive research, the population in this study were final students of the Dental Health Department with a total sampling method totaling 41 respondents. The data collection technique used a questionnaire. The data is presented in the form of a frequency distribution. The results showed the role of the family environment with influential categories (63.5%), the role of the social environment with influential categories (82.9%), and the role of entrepreneurial interest with interested categories (70.7%). The family environment and social environment are influential in shaping students' interest in entrepreneurship in the UKGS field and students' business interest in doing entrepreneurship in the UKGS field in the Department of Dental Health is interested. The role of the family environment, social environment and interest can have a positive impact on students' entrepreneurship.